A Chromosome-Scale Assembly of the Garden Orach (Atriplex hortensis L.) Genome Using Oxford Nanopore Sequencing - Hunt, Spencer P.; Jarvis, David E.; Larsen, Dallas J.; Mosyakin, Sergei L.; Kolano, Bozena A.; Jackson, Eric W.; Martin, Sara L.; Jellen, Eric N.; Maughan, Peter J. (Frontiers in Plant Science, 2020)
Atriplex hortensis (2n = 2x = 18, 1C genome size ~1.1 gigabases), also known as garden orach and mountain-spinach, is a highly nutritious, broadleaf annual of the Amaranthaceae-Chenopodiaceae alliance (Chenopodiaceae sensu stricto, subfam. Chenopodioideae) that has spread in cultivation from its native primary domestication area in Eurasia to other temperate and subtropical regions worldwide. Atriplex L. is a highly complex but, as understood now, a monophyletic group of mainly halophytic and/or xerophytic plants, of which A. hortensis has been a vegetable of minor importance in some areas of Eurasia (from Central Asia to the Mediterranean) at least since Antiquity. Nonetheless, it is a crop with tremendous nutritional potential due primarily to its exceptional leaf and seed protein quantities (approaching 30%) and quality (high levels of lysine). Although there is some literature describing the taxonomy and production of A. hortensis, there is a general lack of genetic and genomic data that would otherwise help elucidate the genetic variation, phylogenetic positioning, and future potential of the species. Here, we report the assembly of the first high-quality, chromosome-scale reference genome for A. hortensis cv. ‘Golden.’ Long-read data from Oxford Nanopore’s MinION DNA sequencer was assembled with the program Canu and polished with Illumina short reads. Contigs were scaffolded to chromosome scale using chromatin-proximity maps (Hi-C) yielding a final assembly containing 1,325 scaffolds with a N50 of 98.9 Mb – with 94.7% of the assembly represented in the nine largest, chromosome-scale scaffolds. Sixty-six percent of the genome was classified as highly repetitive DNA, with the most common repetitive elements being Gypsy- (32%) and Copia-like (11%) long-terminal repeats. The annotation was completed using MAKER which identified 37,083 gene models and 2,555 tRNA genes. Completeness of the genome, assessed using the Benchmarking Universal Single Copy Orthologs metric, identified 97.5% of the conserved orthologs as complete, with only 2.2% being duplicated, reflecting the diploid nature of A. hortensis. A resequencing panel of 21 wild, unimproved and cultivated A. hortensis accessions revealed three distinct populations with little variation within subpopulations. These resources provide vital information to better understand A. hortensis and facilitate future study.